PALESTINIAN PERSPECTIVES ON FOREIGN AID - Awashreh, Raed (International Journal of Research -GRANTHAALAYAH, 2020)
Although Palestinian non-government organizations (NGOs) are hiring some employees and supply money to local market, this article argues that NGOs are moving within the political place of donor’s agenda meaning western governments’ agenda. The historical trends in funding NGOs in the occupied Palestinian territory essentially aim at ending the Palestinian struggle against occupation and encouraging Palestinian masses and institutions to de-politize their agendas and forsake their national goals. In other words, foreign aid has no problem with the continuation of Israeli occupation or that Palestinians never have a (sovereign) state. All indications show that what paramount to donors since the start of peace process is keeping Israel safe and maintaining a limited Palestinian authority with no capacity to pose a threat against Israel. From the Palestinians side, disagreement on foreign aid among them based on funds source UN fund is acceptable, other different between USAID and European funds, other differentiate between government and nongovernmental funds.